2019
DOI: 10.1093/tas/txz027
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of biochar on diet digestibility and methane production from growing and finishing steers

Abstract: Abstract The objectives of these studies were to evaluate the effects of biochar (0%, 0.8%, or 3% of diet dry matter) on diet digestibility and methane and carbon dioxide production from cattle on growing and finishing diets. The growing diet consisted of 21% brome hay, 20% wheat straw, 30% corn silage, 22% wet distillers grains plus solubles, and 7% supplement. The finishing diet consisted of 53% dry-rolled corn, 15% corn silage, 25% wet distillers grains plus s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 16 publications
7
16
0
Order By: Relevance
“…However, there were no associated benefits on apparent nutrient digestibility observed in the present study. This finding is consistent with Winders et al (10) who observed no changes in the total tract digestibility of steers fed either a high forage or high concentrate diet containing biochar at 3% of DM. Counter to this lack of effect, Van et al (38) found that digestibility of DM, OM, and CP were improved, and N retention increased in growing goats fed 0.5 and 1 g/kg BW of bamboo charcoal.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, there were no associated benefits on apparent nutrient digestibility observed in the present study. This finding is consistent with Winders et al (10) who observed no changes in the total tract digestibility of steers fed either a high forage or high concentrate diet containing biochar at 3% of DM. Counter to this lack of effect, Van et al (38) found that digestibility of DM, OM, and CP were improved, and N retention increased in growing goats fed 0.5 and 1 g/kg BW of bamboo charcoal.…”
Section: Discussionsupporting
confidence: 92%
“…Although previous studies have found positive responses to a rice husk biochar (8), the present study utilized a pine EB due to its mass availability across the northern hemisphere. However, pine was the biomass used by both Saleem et al (1) and Winders et al (10) and the biochar still differed in surface area, bulk density and pH. These factors may affect the activity of EB within the rumen and subsequent metabolic responses in both the microbial population and the host animal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the enormously high addition of 9% cannot be considered as viable as this would surely impact feed digestibility on the long term. Winders et al (2019) did not detect any significant reductions on methane emissions in steers over a 23 h period when using the more realistic biochar supplement rates of 0.8% and 3%.…”
Section: Resultsmentioning
confidence: 70%
“…Winders et al [61] evaluated the effects of a 0.8% and 3% BC diet inclusion for steers on growing and finishing diets. Digestibility, and CH 4 and CO 2 production from cattle were investigated.…”
Section: Biochar As a Feed Additivementioning
confidence: 99%